2024
DOI: 10.1038/s41586-023-06971-z
|View full text |Cite
|
Sign up to set email alerts
|

SHR and SCR coordinate root patterning and growth early in the cell cycle

Cara M. Winter,
Pablo Szekely,
Vladimir Popov
et al.

Abstract: Precise control of cell division is essential for proper patterning and growth during the development of multicellular organisms. Coordination of formative divisions that generate new tissue patterns with proliferative divisions that promote growth is poorly understood. SHORTROOT (SHR) and SCARECROW (SCR) are transcription factors that are required for formative divisions in the stem cell niche of Arabidopsis roots1,2. Here we show that levels of SHR and SCR early in the cell cycle determine the orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…In our scRNA-seq profiles, we did not detect any enrichment of known cell identity markers in a given phase of the cell cycle. Thus, we have no evidence that short G1s could bypass differentiation signals, although we cannot rule out that cell fate markers are induced synchronously but transcribed at different rates or regulated at another level as has been shown for some specific contexts in plants 3,4 . Nonetheless, our experiments clearly associate rapid G1 phases and coordinated G1 exit with the competence to reprogram cell fate across cell types.…”
Section: Reprogramming Plant Cells Divide Rapidly By Truncating G1mentioning
confidence: 77%
See 1 more Smart Citation
“…In our scRNA-seq profiles, we did not detect any enrichment of known cell identity markers in a given phase of the cell cycle. Thus, we have no evidence that short G1s could bypass differentiation signals, although we cannot rule out that cell fate markers are induced synchronously but transcribed at different rates or regulated at another level as has been shown for some specific contexts in plants 3,4 . Nonetheless, our experiments clearly associate rapid G1 phases and coordinated G1 exit with the competence to reprogram cell fate across cell types.…”
Section: Reprogramming Plant Cells Divide Rapidly By Truncating G1mentioning
confidence: 77%
“…In the Arabidopsis sepal, giant cells are specified when MERISTEM LAYER 1 ( ML1 ) expression exceeds a threshold level during G2/M phase of the cell cycle 3 . Recent work has shown that high protein levels of the cell fate regulators SHORT ROOT (SHR) and SCARECROW (SCR) at a specific phase of the cell cycle determine the polarity of a formative division in the root 4 . In the stomatal lineage, asymmetric and symmetric cell divisions are mediated by the expression of a series of master regulator basic helix-loop-helix (bHLH) transcription factors that concomitantly regulate cell identity (reviewed in 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SHR-SCR complex promotes the expression of WOX5, which plays a pivotal role in maintaining QC identity and preventing the differentiation of surrounding stem cells [26]. The levels of SHR and SCR early in the cell cycle determine the orientation of the division plane, resulting in either formative or proliferative cell division [55].…”
Section: Key Factors In the Maintenance Of Ram Activitymentioning
confidence: 99%